Fulfillment of the Constitutional Rights of Persons with Disabilities in Central Java Province Civil Servant Candidate Selection 2019 - Sofiani, Trianah; Latipah, Dwi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Issuance of a State Administrative Decree by the Regional Secretariat of Central Java Province to people with disabilities on behalf of M. Baihaqi who was considered discriminatory during the 2019 Central Java National Civil Service Candidate selection who was declared not to have passed due to the requirements for the type of disability and educational qualifications being inappropriate. Administrative efforts have been taken to regain his rights but have been unsuccessful. Until finally resorting to litigation by filing a lawsuit with PTUN Semarang and an appeal to PT TUN Surabaya but it was declared not accepted. Then in the cassation the Supreme Court granted all the claims and asked the defendant to revoke the issued State Administrative Decree and process M. Baihaqi's in the Central Java National Civil Service Candidate selection 2019. The research method used is normative juridical with statutory, conceptual and case approaches. The research results show that the fulfillment of the constitutional rights of persons with disabilities in the 2019 Central Java Civil Servant Candidate Selection is considered not optimal because the solution provided by the defendant as an implementation of the Supreme Court's decision is not in accordance with the Supreme Court's decision.